Prediction of risk of recidivism in a sample of Spanish children offenders. Evidence of validity of SAVRY - García-García, Juan (Consorcio de Universidades Mexicanas A.C., 2016)
Prediction of risk of recidivism in a sample of Spanish young offenders. Validity evidence of SAVRY. The use of instruments for predicting the risk of recidivism in young offenders is increasingly widespread among professionals and researchers, causing the increase in the number of instruments specifically developed for juvenile offenders. Among the instruments for predicting the risk of recidivism created for youth highlights the Structured Assessment of Violence Risk in Youth (SAVRY. Borum, Bartel, & Forth, 2002, 2006). In this paper an approach to the predictive validity of SAVRY in its application offenders spanish young is presented. The sample consists of a total of 594 juveniles with court case in Juvenile Court of Almeria (Spain), aged between 14 and 18 at the time of the commission of antisocial behavior punished. 85.4% of juveniles were male and 79% of spanish nationality. The results show that the SAVRY instrument has a good predictive capacity.